Corpo vivido e corpo pulsional: uma leitura de Merleau-Ponty e Freud. - Lucena, Francisco Almeida de (2012)
Empiricism and intellectualism are distinct perspectives which, taking as a starting point the modernity with the thought of Rene Descartes and the English empiricists, guide the epistemological statute of various areas of scientific knowledge. In the contemporaneity, such perspectives are observed in areas such as anatomy, physiology, medicine, biology, psychology, among others. The comprehension of the body, which is influenced by the cited perspectives, often suffers from a reductionism which one moment tends to the psychologism, and one another to physicism. An approach which proposes an integral understanding of the body needs to take into account the various and complex aspects which compose it. The thought of Maurice Merleau-Ponty and of Sigmund Freud allows a reading of the body as a live and pulsatory instance which resists to the pretension of an objective definition of the body. The subjectivity which permeates all the corporal parts and mechanisms, as well as the pulsional forces which act on them, subvert all and any pretension of a reductionist framework, and impose on the corporeity a living and amazing character.